Synthesis and Microbial Activity of 5-(2-Methyl-4-N-cyanoethyl-Nbenzenesulphonyl aminobenzylidene)rhodanine and its Metal Complexes - Gandhi, Sandhya; Dave Gautam, Mangla (Asian Journal of Chemistry, 2010)
Synthesis of 5-(2-methyl-4-N-cyanoethyl-N-benzenesulphonyl aminobenzylidene)rhodanine (I) by the reaction of 2-methyl-4-N-cyanoethyl-N-benzenesulphonyl aminobenzaldehyde (II) and rhodanine (III) is described. Synthesized rhodanine derivative and its metal complexes were screened for their microbial activities.